2014
DOI: 10.1016/j.mvr.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nanoparticle delivery in microcirculation using a microfluidic device

Abstract: This work focuses on the characterization of particle delivery in microcirculation through a microfluidic device. In microvasculature the vessel size is comparable to that of red blood cells (RBCs) and the existence of blood cells largely influences the dispersion and binding distribution of drug loaded particles. The geometry of the microvasculature leads to non-uniform particle distribution and affects the particle binding characteristics. We perform an in vitro study in a microfluidic chip with micro vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…This increased binding density of particles with higher antibody coating is consistent with other studies and our previous work. 21,48,49 Previous studies have reported the binding kinetics of particles with higher anti-ICAM-1 coating density to be significantly faster, 48,50 which could be valid for our study as our maximum particle flow time is only 6 min. The particle binding density decreased when the FSS increased from 6 to 12 dyn/cm 2 for both anti-ICAM-1 coating density cases.…”
Section: Baoec Stress Fiber Alignment Under Fsssupporting
confidence: 61%
See 2 more Smart Citations
“…This increased binding density of particles with higher antibody coating is consistent with other studies and our previous work. 21,48,49 Previous studies have reported the binding kinetics of particles with higher anti-ICAM-1 coating density to be significantly faster, 48,50 which could be valid for our study as our maximum particle flow time is only 6 min. The particle binding density decreased when the FSS increased from 6 to 12 dyn/cm 2 for both anti-ICAM-1 coating density cases.…”
Section: Baoec Stress Fiber Alignment Under Fsssupporting
confidence: 61%
“…An increase in FSS reduced the available time for particles to diffuse/marginate towards the endothelial cell surface, which reduced their binding density as observed in other studies. 48 The particle binding density also does not reduce for FSS > 12 dyn/ cm 2 ( Fig. 6).…”
Section: Baoec Stress Fiber Alignment Under Fssmentioning
confidence: 86%
See 1 more Smart Citation
“…In vitro work by Liu et al found that blood enhances both 210nm and 2µm polystyrene particle binding in microcirculation. The binding density increased threefold more for the 2µm particles compared to the 210nm particles [112]. Eniola-Adefeso et al examined the effect of particle size (500nm to 10µm) on margination propensity in blood and observed an increase in this phenomenon with increasing particle size [101,105].…”
Section: Role Of Blood Elements In Vascular Targetingmentioning
confidence: 99%
“…The advantages of microreactors are their high surface area to volume ratio, tunable inner-wall properties, versatile flow-orientation, and flexible-structural designs [13][14][15][16][17][18][19][20][21]. In addition, diffusive exchange of heat and mass can be achieved within small length scales.…”
Section: Introductionmentioning
confidence: 99%